Freestyle Bioprosthetic Valves: Clinical Outcomes, Surgical Techniques, and Future Directions - Ermal Likaj; Alessia Mehmeti; Jacob Zeitani; Selman Dumani; Fjorba Mana; Aferdita Veseli; Esmerilda Bulku; Altin Veshti (Albanian Journal of Trauma and Emergency Surgery, 2025)
Introduction: The Freestyle® stentless porcine aortic root (Medtronic, Minneapolis, MN) has emerged as a valuable option for aortic valve replacement (AVR), offering superior hemodynamics compared to stented bioprostheses and eliminating the need for lifelong anticoagulation required with mechanical valves. Derived from a porcine aortic root, the Freestyle valve allows for versatile implantation techniques, including subcoronary, root inclusion, and full root replacement. While the Freestyle valve demonstrates excellent hemodynamics and benefits, as well as acceptable long-term survival, challenges remain regarding structural valve deterioration (SVD) in younger patients and technical complexities during implantation. These technical complexities include the need for precise surgical expertise, the stentless nature of the prosthesis, dense adhesions, and circumferential calcification of the porcine root. Emerging technologies, such as advanced anti-calcification treatments and tissue engineering, may further enhance its durability. In this article, we present two illustrative cases from our institution to highlight these challenges and discuss surgical strategies, as well as synthesize current evidence and discuss future directions for stentless bioprosthetic valves.